E-commerce transactions among consumers in the webpage of small business in Malaysia: a validity measurement model - Abdullah, Moha Asri; Juhdi, Nurita; Mohamad, Noorihsan; Azam, Ferdous (UUNZ Institute of Business, 2014)
Studies focusing on factors influencing the consumer use of e-commerce for purchasing from small and medium scale enterprises remain very limited, especially in developing countries. This study attempts to address part of this limitation by developing a measurement model for consumer use of e-commerce for small enterprises in Malaysia. The study employed a quantitative research method using a primary data collected through self-administered questionnaires involving a sample of 502 respondents from various places in Malaysia. The results suggest that the use of e-commerce for small businesses is influenced by five interrelated factors where each indicator has a nonzero loading on its hypothesised or targeted factor. The findings of this study will assist small business owners and managers to provide their services more efficiently.